Peningkatan Literasi Keuangan melalui Reksa Dana Syariah sebagai Upaya Mendorong Inklusi Keuangan Syariah di Indonesia - Miftahul Fauzi; Uky Zaza Agustiana; Dini Selasi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Financial literacy is an individual's ability to understand, analyze, and use financial information to make effective decisions. In the context of Islamic finance in Indonesia, low financial literacy is a major challenge in increasing financial inclusion. Islamic mutual funds, as one of the sharia-based investment instruments, offer an opportunity to bridge the gap between financial literacy and inclusion. Islamic mutual funds have the advantages of transparent sharia principles, wider accessibility, and diversified risks. This study aims to explore the role of Islamic mutual funds in increasing public financial literacy while encouraging Islamic financial inclusion. The methodology used includes secondary data analysis, surveys, and interviews with stakeholders, such as financial industry players, regulators, and the community. The results of the study show that education about Islamic mutual funds can consistently increase public understanding of Islamic financial products. In addition, Islamic mutual funds also have the potential to expand public access to Islamic financial services, especially among the younger generation and underserved groups. Integration of financial literacy programs based on sharia mutual funds with the support of regulations and digital technology can be a strategic step to strengthen the sharia financial ecosystem in Indonesia, thereby supporting more inclusive and sustainable financial inclusion.